Morphological, mechanical and thermal properties of PA6 nanocomposites Co-Incorporated with Nano-Al2O3 and graphene oxide fillers. (3rd February 2020) - Huang, Huan; Yan, Lei; Guo, Yi; Lin, Hai Lan; Chen, Lin; Yang, Li Fei; Xie, Yu Jia; Bian, Jun
Abstract: In this paper, the surface hydroxylation modification of nano-alumina (nano-Al2 O3 ) to result nano-Al2 O3 –OH and the chemical modification of graphene oxide (GO) by using silane coupling agent to produce GO-KH560 were first carried out respectively, followed by solution compounding to synthesis a novel three-dimensional functional hybrid filler (nano-Al2 O3 –OH/GO-KH560), and then polyamide 6 (PA6)/nano-Al2 O3 –OH/GO-KH560 (abbreviated as P-A-OH -G-KH560 ) thermally conductive nanocomposites were fabricated by melt blending technique and investigated for its morphological, mechanical and thermal properties. Morphological characterization revealed better dispersion of nano-Al2 O3 and GO in the PA6 nanocomposites, which is attributed to the improved interfacial interaction between the PA6 and hybrid fillers. Loading of the hybrid fillers in the PA6 nanocomposites resulted in the significant improvement in mechanical properties such as tensile strength and elastic modulus and this effect is more pronounced on the increasing the hybrid fillers loading amount, when compared to the PA6 and pristine nano-Al2 O3 filled system. Differential scanning calorimetric analysis showed that the crystallization of the PA6 nanocomposites was improved. The thermal conductivity of the P-A-OH -G-KH560 (100/5/0.8) nanocomposite increased by 86.13% compared with that of pure PA6. In summary, PA6 nanocomposites with fairly good mechanical and thermal conductivity are obtained at low filler contents. Graphical abstract: Image 1 Highlights: Hybrid filler containing Al2 O3 and GO nanofillers were introduced into PA6 matrix by direct melt blending. Strong interactions between PA6/nano-Al2 O3 /GO allowed homogeneous dispersion of nano-Al2 O3 /GO in the polymer matrix. The thermal conductivity of the PA6 nanocomposites were enhanced significantly. The addition of nano-Al2 O3 –OH and GO-KH560 hybrid nanofillers effectively improved the performance of PA6, and an excellent nanocomposites which combines mechanical properties and thermal conductivity at a low content is obtained.